Cardiovascular disease, mortality, and magnesium in chronic kidney disease: growing interest in magnesium-related interventions - Ryota Ikee (Renal Replacement Therapy, 2018)
Abstract Magnesium (Mg) is an essential element that plays pivotal roles in a number of biological processes in the human body. Hypomagnesemia is involved in the pathophysiology of hypertension, vascular calcification, and metabolic derangements including diabetes mellitus and dyslipidemia, which are all risk factors for cardiovascular disease, the leading cause of mortality and morbidity in patients with chronic kidney disease (CKD). Hypomagnesemia is also associated with the development and progression of CKD. As CKD advances, renal Mg excretion decreases and hypermagnesemia emerges in end-stage renal disease (ESRD). In addition, dialysates with high Mg concentrations, which were used in the early era of dialysis therapy, increased the risk of hypermagnesemia, and thus, the dialysate Mg composition has since been reduced. Accordingly, dialysis patients in the modern era commonly have normomagnesemia or even hypomagnesemia. The relationships between hypomagnesemia and cardiovascular disease and mortality have been increasingly reported in observational studies in CKD/ESRD. However, these relationships may be attenuated by a patient’s race or region. Although dialysates with higher Mg concentrations or Mg-containing phosphate binders appear to be promising in this setting, only a few interventional studies have examined the effects of Mg supplementation on cardiovascular lesions. Furthermore, the effects of Mg supplementation on mortality have not yet been investigated as a primary end-point in randomized controlled trials. Further studies are required in order to establish the efficacy and safety of Mg in CKD patients.